Standoff [videorecording (DVD)] - Alleca, Adam, 1983-; Fishburne, Laurence, III, 1961-; Jane, Thomas; Ballentine, Ella, 2001- (Lionsgate, 2016)
A troubled veteran gets a chance at redemption by protecting a twelve-year-old girl from an assassin after she witnesses a murder.